A FEAST OF CIVILIZATIONS: THE LIFE AND MIND OF TOSHIHIKO IZUTSU - Anwar Ibrahim, (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2024)
Toshihiko Izutsu’s contributions to the world of the intellect, theology and philosophy have been so immense, expansive and multifarious that it is a travesty to attempt to single out his most significant contributions. That’s because his works are so seamlessly interconnected that it’s almost impossible to segregate or compartmentalise them without appearing to have taken an arbitrary position.